Pembuktian dalam kes jenayah syariah di mahkamah syariah Malaysia: isu dan penyelesaian - Ramlee Saad, Zulfakar (Dewan Bahasa Dan Pustaka, 2015)
Proof is an important element in a judicial process, thus deep understanding in the principles of evidence is crucial. Some of these principles are quite rigid and other are very flexible. The flexibility of the principles could easily accommodate current and complex issues. Furtunetely, most of these principles are already embodied in the Act or Enactments. Of course, no code is perfect and thus open to many loopholes or lacuna. Therefore, correct understanding regarding principles of Islamic evidence is prerequise in implementing this Act in the Syariah court. This article discusses some of the current issues in criminal prosecution in the Syariah court in Malaysia.